2017
DOI: 10.4172/2379-1764.1000230
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Model to Study the Role of microRNAs in Glomerular Function and Disease

Abstract: The zebrafish physiology of many organs including the kidney is very similar to that of human beings. Zebrafish develop from a fertilized egg to free-swimming larvae in only 48 h. The zebrafish larvae's correlate for the human kidney is the pronephros consisting of two nephrons with glomeruli fused at the embryo mid-line ventral to the dorsal aorta [1] ( Figure 1a).The glomerular filtration barrier of the pronephros is ultrastructurally almost indistinguishable from a mammalian glomerulus with interdigitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With their seed sequence they bind specifically to target mRNAs, thereby blocking translation and/or facilitating mRNA degradation 1 . In the recent past it could have been shown that microRNAs play a pivotal role in kidney development, physiology and pathology [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…With their seed sequence they bind specifically to target mRNAs, thereby blocking translation and/or facilitating mRNA degradation 1 . In the recent past it could have been shown that microRNAs play a pivotal role in kidney development, physiology and pathology [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%